The dynamics of fiscal deficit and current account in 12 SADC countries - Kondo, Talent; Mutsvangwa, Simba (Goodwood Publishing, 2025)
Purpose: This study examines the relationship between fiscal deficits and current account deficits in SADC countries. Methods: A panel analysis using a random-effects model with secondary data from 2009 to 2020 was employed. Results: Higher fiscal deficits affected current account deficits in the SADC region. Real interest rates and trade openness are critical determinants of both deficits. Contributions: This study enhances the understanding of macroeconomic imbalances in the SADC region, guiding policymakers in creating tailored policy frameworks for economic stability and sustainable development. Novelty: The study provides a comprehensive analysis of the relationship between fiscal deficit and current account deficits in Southern African Development Community (SADC) 12-member countries, offering significant insights into the macroeconomic dynamics of the region. A panel analysis using a random effects model with data spanning September 2009 to December 2020 was employed, capturing trends and individual country effects. This study provides a robust examination of common trends and individual country effects, enriching the understanding of how these macroeconomic variables are important within the SADC context. Its emphasis on tailored policy frameworks to address fiscal and external imbalances reflects a forward-looking approach, offering practical guidance for policymakers striving to enhance economic stability and sustainable development within the SADC region. As an area for further study, the same research can be replicated in BRICKS countries and a comparative analysis can be conducted for a broader analysis.